ANALYSIS THE WORKING SPACE AND KINEMATICS OF THE MICRO 3-PSP PARALLEL MECHANISM - XIE ZheDong; JIA YuXuan; SHAO Qi; GAN XinJi (Jixie qiangdu)
To satisfied the requirement of the laser angle adjustment,this paper proposed a micro 3-PSP parallel robot with a special structure with the diameter of the static platform is 50 mm,the height of the system is about 74 mm-80 mm;Using the‘closed-loop vector method’to set up the inverse kinematics model of the parallel robot.Then get the solution of the inverse kinematics.On the basis of the inverse kinematics solution,the constraint of the shaft movement and the parameters of the mechanism,we get the 3 D working space of the parallel robot via MATLAB.Finally,we simulated the kinematics of the parallel robot by Solid Works and Adams,and the results show that the 3-PSP parallel robot could accomplish three dimensions moving with smooth.